2021
DOI: 10.1111/psyp.13795
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus–response learning and expected reward value enhance stimulus cognitive processing: An ERP study

Abstract: Reward affects our attention to stimuli, prioritizing those that lead to high‐value outcomes. Recently, it has been suggested that such reward‐related cognitive prioritization might be associated with the process of learning new stimulus–response (S‐R) associations, because both are acquired through extended reward training, and once established, they are hard to overcome. We used event‐related potentials (ERP) to analyze the contribution of S‐R links to the formation of reward‐related cognitive prioritization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
(160 reference statements)
1
2
0
Order By: Relevance
“…In other words, this manipulation triggered habitual processes, facilitating the association between specific stimuli and specific motor commands. In agreement with our results, using a different task, but manipulating the consistency of response mappings, Molinero et al (2021) found that reward-related cognitive prioritization was stronger when a constant response pattern was kept. Also, Hardwick, Forrence, Krakauer & Haith (2019) found that habits were produced when specific S-R associations were always executed with the same motor command.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, this manipulation triggered habitual processes, facilitating the association between specific stimuli and specific motor commands. In agreement with our results, using a different task, but manipulating the consistency of response mappings, Molinero et al (2021) found that reward-related cognitive prioritization was stronger when a constant response pattern was kept. Also, Hardwick, Forrence, Krakauer & Haith (2019) found that habits were produced when specific S-R associations were always executed with the same motor command.…”
Section: Discussionsupporting
confidence: 91%
“…In their version of the two-stage task, da Silva & Hare (2020) used first- and second-stage options that randomly swapped sides from trial to trial. This aspect of the procedure may prevent the formation of strong associations between these stimuli and specific motor commands (Molinero et al, 2021; Verleger et al, 2016, 2018). This is an aspect that may hinder the execution of habitual responses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it seems that the model-free component of these models can be capturing the formation of incorrect models, rather than the operation of the habit system (da Silva and Hare, 2020). Thus, the standard two-step sequentialdecision task may not be sensitive enough to capture key processes involved in outcomeinsensitive habits, perhaps because participants have to choose between multiple outcomes with varying reward rates (Molinero et al, 2021;Wood and Rünger, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothetical operation is associated with the reactivation of the established S‐R links (Verleger, 2020). Recent experimental investigations have explicitly tested the reflection of S‐R links in the target P3 waves demonstrating that stronger S‐R links elicit larger P3 amplitude (Molinero et al., 2021; Verleger, 2020). The second hypothetical operation is related to the allocation of perceptual and/or attentional resources (McCarthy & Donchin, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the S‐R hypothesis (Molinero et al., 2021; Verleger, 2020), we hypothesize that at least one of P3 subcomponents is closely associated with the strength of S‐R links. Moreover, following the action selection hypothesis (Hillyard & Kutas, 1983; Pritchard et al., 1999) we speculate that at least one of the extracted components is closely associated with GO/NOGO responses.…”
Section: Introductionmentioning
confidence: 99%